Advancing regulatory aircraft nvPM sampling and measurement practices: Uncertainty quantification and recommendations - Eliot Durand; Lukas Durdina; Joseph Harper; Curdin Spirig; Manuel Roth; Greg Smallwood; Mark Johnson; Fergus O.N. Lidstone-Lane; Paul I. Williams; Andrew Crayford (Journal of Aerosol Science, 2026)

Aerosol Delivery of Polyelectrolyte Surfactant—Antimicrobial Nanoparticles to the Lungs - Yadiel Varela Soler; Amanda S. Padilla-López; Sughosha Rao; Leonardo Calderon; Gediminas Mainelis; Olga Garbuzenko; Tamara Minko; David I. Devore; Charles M. Roth (Pharmaceutical Research, 2026)
Background Lung infections affect over 80% of adults with cystic fibrosis, with Pseudomonas aeruginosa being a leading pathogen. Although antibiotics are frequently nebulized as standard treatments, the physicochemical environment of the diseased lung often limits their diffusion and overall effectiveness. Our previous studies showed polyelectrolyte surfactants (PS) to be a promising delivery system for cationic antimicrobials in vitro . This study seeks to expand that knowledge by evaluating their potential for nebulized delivery. Methods To achieve this, we evaluated their size and antimicrobial activity following nebulization; in vitro toxicity against epithelial cells and erythrocytes; and biodistribution and expression of inflammation markers following administration to healthy mice. Results The nanoparticle formulation exhibited a mucolytic effect on an artificial mucus model of cystic fibrosis mucus. Following nebulization, nanoparticles retained both their size and biological activity. Additionally, they displayed no observable toxicity in vitro against either human lung epithelial cells or erythrocytes; instead, epithelial cells treated with PS-based nanoparticles showed increased cell viability. Following administration of these formulations to mice via inhalation, over 70% of the recovered nanoparticles were retained in the lungs 24 h after treatment, with a small fraction being uniformly distributed to other tissues. A screen of key inflammatory cytokines revealed that inhalation treatment led to a slight increase of IL-6 in the liver and IL-18 in the spleen. These increases seem to be consistent with a minor inflammatory response. Conclusion Overall, the results suggest that PS are a promising nanotechnology for the pulmonary delivery of cationic drugs.

Click beetles (Elateridae) identify conservation units in Oriental and European beech forests - Giorgi Mamadashvili; Andrea Jarzabek-Müller; Hazan Alkan Akinci; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Diedus; Lars Drössler; Jamshid Eslamdoust; Kostadin B. Georgiev; Tigran Ghrejyan; et al. (Journal of Insect Conservation, 2025)
Beech trees form major parts of lowland temperate forests in the Western Palearctic. To protect biodiversity, many beech forests have been designated as World Heritage Sites or established as networks of beech forest reserves. However, the insect communities within these protected forests have not been well explored. In this study, elaterids (Elateridae, Coleoptera) in 26 beech forests, from France in the west to Iran in the east, were sample to identify conservation clusters and hotspots of biodiversity. Sampling was mostly carried out using window traps and all specimens were identified to the species level. A total of 118 species were identified including one previously unreported species. Community composition analyses that focused on rare species identified five clusters comprising distinct communities: (i) the Hyrcanian Forest in Iran, (ii) the Lesser Caucasus in Türkiye, Georgia and Armenia, (iii) the Greater Caucasus in Georgia, (iv) the Pyrenees and (v) a cluster made up of forests from Central Europe, the Balkan region and the Carpathians. After controlling for sampling effort (individuals), the highest richness was found in the Caucasus region. The proportion of endemics was highest in the Oriental beech forests of the Caucasus and in Hyrcanian forests. These findings highlight the unique biodiversity of beech forests and support calls for intensified conservation actions in beech forests, particularly in the Caucasus and Hyrcanian regions, which should be prioritized for conservation efforts, due to their unique fauna. Implications for insect conservation Our study underscores the importance of protecting beech forests, especially in the Caucasus and Hyrcanian regions, as they host unique and endemic insect species critical for biodiversity conservation.

Distinct fungal and bacterial responses to fire severity and soil depth across a ten-year wildfire chronosequence in beetle-killed lodgepole pine forests - Marcos V. Caiafa; Amelia R. Nelson; Thomas Borch; Holly K. Roth; Timothy S. Fegel; Charles C. Rhoades; Michael J. Wilkins; Sydney I. Glassman (Forest Ecology and Management, 2023)

Drivers of tree-related microhabitat profiles in European and Oriental beech forests - Giorgi Mamadashvili; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Deidus; Lars Drössler; Céline Emberger; Kostadin B. Georgiev; Tigran Ghrejyan; Martin M. Gossner; Ruslan Hleb; et al. (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Reassessing Potential for Exotic Larch in Northern United States - David I Maass; Lloyd C Irland; James L Anderson; Kenneth M Laustsen; Michael S Greenwood; Brian E Roth (Journal of Forestry, 2020)
Abstract Field measurements of operational plantations and research plots demonstrate that growth rates of exotic larches in unmanaged stands can exceed 12 m3 per hectare per year in Maine and elsewhere. This paper briefly reviews the recent history of exotic larch (Larix decidua, L. kaempferi, and L. × marschlinsii) in northeastern United States and Canada. Stands can be commercially thinned as early as 15 years; further thinnings add to significant volume accumulation, based on stand table projections. Genetic development of the hybrid (L. × marschlinsii) could yield additional volume. Even at current low stumpage values, exotic larch plantations offer positive returns at realistic discount rates. In map form, we report a current inventory of known trials and operational plantings across the Northern United States, including adjacent Canada.

Multiple stressor effects on coral reef ecosystems - Joanne I. Ellis; Tahira Jamil; Holger Anlauf; Darren J. Coker; Joao Curdia; Judi Hewitt; Burton H. Jones; George Krokos; Benjamin Kürten; Dasari Hariprasad; Florian Roth; Susana Carvalho; et al. (Global Change Biology, 2019)
Global climate change has profound implications on species distributions and ecosystem functioning. In the coastal zone, ecological responses may be driven by various biogeochemical and physical environmental factors. Synergistic interactions can occur when the combined effects of stressors exceed their individual effects. The Red Sea, characterized by strong gradients in temperature, salinity, and nutrients along the latitudinal axis provides a unique opportunity to study ecological responses over a range of these environmental variables. Using multiple linear regression models integrating in situ, satellite and oceanographic data, we investigated the response of coral reef taxa to local stressors and recent climate variability. Taxa and functional groups responded to a combination of climate (temperature, salinity, air‐sea heat fluxes, irradiance, wind speed), fishing pressure and biogeochemical (chlorophyll a and nutrients ‐ phosphate, nitrate, nitrite) factors. The regression model for each species showed interactive effects of climate, fishing pressure and nutrient variables. The nature of the effects (antagonistic or synergistic) was dependent on the species and stressor pair. Variables consistently associated with the highest number of synergistic interactions included heat flux terms, temperature, and wind speed followed by fishing pressure. Hard corals and coralline algae abundance were sensitive to changing environmental conditions where synergistic interactions decreased their percentage cover. These synergistic interactions suggest that the negative effects of fishing pressure and eutrophication may exacerbate the impact of climate change on corals. A high number of interactions were also recorded for algae, however for this group, synergistic interactions increased algal abundance. This study is unique in applying regression analysis to multiple environmental variables simultaneously to understand stressor interactions in the field. The observed responses have important implications for understanding climate change impacts on marine ecosystems and whether managing local stressors, such as nutrient enrichment and fishing activities, may help mitigate global drivers of change.

Integration of sudden death syndrome resistance loci in the soybean genome - Hao-Xun Chang; Mitchell G. Roth; Dechun Wang; Silvia R. Cianzio; David A. Lightfoot; Glen L. Hartman; Martin I. Chilvers (Theoretical and Applied Genetics, 2018)

Glutamate Release Machinery Is Altered in the Frontal Cortex of Rats with Experimental Autoimmune Encephalomyelitis - Natalí L. Chanaday; A. Alejandro Vilcaes; Ana L. de Paul; Alicia I. Torres; Alicia L. Degano; German A. Roth (Molecular Neurobiology, 2015)

Impact of raw pig slurry and pig farming practices on physicochemical parameters and on atmospheric N2O and CH4 emissions of tropical soils, Uvéa Island (South Pacific) - E. Roth; P. Gunkel-Grillon; L. Joly; X. Thomas; T. Decarpenterie; I. Mappe-Fogaing; C. Laporte-Magoni; N. Dumelié; G. Durry (Environmental Science and Pollution Research, 2014)

Neonatal steroids induce a down-regulation of tenascin-C and elastin and cause a deceleration of the first phase and an acceleration of the second phase of lung alveolarization - Matthias Roth-Kleiner; Thomas M. Berger; Sandrine Gremlich; Stefan A. Tschanz; Sonja I. Mund; Martin Post; Marco Stampanoni; Johannes C. Schittny (Histochemistry and Cell Biology, 2014)

Is it possible to detect dendrite currents using presently available magnetic resonance imaging techniques? - William I. Jay; Ranjith S. Wijesinghe; Brain D. Dolasinski; Bradley J. Roth (Medical & Biological Engineering & Computing, 2012)

Autistic Traits Below the Clinical Threshold: Re-examining the Broader Autism Phenotype in the 21st Century - E. Sucksmith; I. Roth; R. A. Hoekstra (Neuropsychology Review, 2011)

Amisulpride is a potent 5-HT7 antagonist: relevance for antidepressant actions in vivo - Atheir I. Abbas; Peter B. Hedlund; Xi-Ping Huang; Thuy B. Tran; Herbert Y. Meltzer; Bryan L. Roth (Psychopharmacology, 2009)

Population genetics and conservation of the threatened southeastern beach mouse (Peromyscus polionotus niveiventris): subspecies and evolutionary units - Jacob F. Degner; I. Jack Stout; James D. Roth; Christopher L. Parkinson (Conservation Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The Occurrence and Distribution of Selected Trace Elements in the Upper Rio Grande and Tributaries in Colorado and Northern New Mexico - H. E. Taylor; R. C. Antweiler; D. A. Roth; T. I. Brinton; D. B. Peart; D. F. Healy (Archives of Environmental Contamination and Toxicology, 2001)

Isolation of a petite mutant from a histidine auxotroph of Candida albicans and its characterization - Z. Roth-Ben Arie; Z. Altboum; I. Berdicevsky; E. Segal (Mycopathologia, 1998)

Trisomy associated with loss of maturation capacity in a long-term embryogenic culture of Abies alba - R. Roth; I. Ebert; J. Schmidt (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)